Prevalence of non-alcoholic fatty liver disease in urban adult population in a tertiary care center, Chennai - Mary Chandrika Anton; B Shanthi; Chaganti Sridevi (Wolters Kluwer Medknow Publications, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is becoming one of the most common liver diseases among the Indian population. The predisposing factors for NAFLD are diet, lifestyle modifications, and lack of exercise. There is a paucity of research on NAFLD in the South Indian population. Hence, the present study aimed to assess the prevalence of NAFLD among the urban adult population in Chennai. Material and Methods: This analytical cross-sectional study was conducted in General Medicine outpatient departments at a tertiary care center in Chennai. The study included 510 non-alcoholic adults (both male and female) aged between 21 and 40 years. Ultrasonography was performed to rule out fatty liver in all participants. All the results obtained were statistically analyzed using SPSS software version 22.0. The frequency was given in percentage. Results: The proportion of participants who screened positive for NAFLD was 61.5%. The participants with higher body mass index (BMI) were found to be significantly 23.09 times higher risk of developing NAFLD. An increase in age was also found to be a predictor of NAFLD. This study also supports that males are more prone to develop NAFLD and are at a 1.59% higher risk of developing the disease than females. Conclusion: Fatty liver has become one of the common non-communicable diseases in India, the high prevalence of NAFLD in the present study supports it. Therefore, people should have regular screening and diagnosis to rule out fatty liver disease. Proper diet patterns and exercise must be followed to prevent fatty liver.